Rheological quantification of bitumen aging : definition of a new sensitive parameter - Peralta, Elvira Joana Ferreira (2010)
Bitumen is undoubtedly the most important material in the construction and rehabilitation of flexible road pavements. By increasing the temperature, bitumen changes from brittle solid, to viscoelastic solid and finally to Newtonian fluid. The rheological characteristics of bitumen also vary greatly due to aging, which is a phenomenon initiated in the phases of production and application of bituminous (asphalt) mixtures and continued during the Iife of road pavements. The aim of this work is to study several rheological parameters in order to evaluate if they are able to quantify the aging of various types of bitumens. Four bitumens from the same distillation column in the refinery, but with different penetration grades, were aged by using the RTFOT method, which simulates the aging of the bitumen during the asphalt mixture production and pavement construction. The original (base) and aged bitumens were characterized with conventional tests used in the paving industry, and the results were compared with the rheological characteristics obtained with small amplitude oscillatory shear tests. Aging was assessed at high temperatures (110ºC to 180ºC) through the activation energy computed from the temperature dependence ofthe Newtonian viscosity. However, the comparison of the characteristic relaxation times extracted from master curves measured at medium/low temperatures (between 25ºC to 80°C), proved to be the most sensitive indicator of bitumen aging.